Socialization of Environmental Road Maintenance in Settlements with the Application of Biopores to Reduce Water Runoff to the Road Surface - Karyawan, I Dewa Made Alit; Negara, I Dewa Gede Jaya; Yasa, I Wayan; Mahendra, Made; Joniarta, I Wayan (Pascasarjana Universitas Mataram, 2024)
As a result of rapid population growth, the Montong Are area in Mandalika Village, Mataram City experienced a change in land use from rice fields to residential land. The main obstacle faced is inadequate drainage due to the low position of the location and the height of the ground water level. Therefore, water often overflows onto the road surface during the rainy season, hampering traffic and causing damage to infrastructure. Water runoff can be reduced and drainage can be improved with the use of low-tech solutions such as biopores. Biopores outreach and training is needed to build a sustainable housing environment and reduce the negative impact of water runoff on road infrastructure. The stages of socialization activities include: Preliminary Survey; Preparation for implementation; Implementation of Socialization; evaluation stage; and Preparation of Reports and Outputs. The socialization activity began with the delivery of material about biopores and discussion, followed by a demonstration on how to make biopores. The community has been successfully educated about biopores and their function in absorbing rainwater into the soil and reducing the possibility of erosion and flooding. The community was very enthusiastic about taking part in the socialization of biopores making activities considering its benefits for use in road maintenance activities. The knowledge gained can increase public awareness of utilizing this concept as a solution that can be applied to overcome the problem of runoff and flooding on the road surface. So that people can actively participate in the construction and maintenance of biopores around where they live because of the benefits they experience